KAJIAN PARTICULATE MATTER DAN KEBISINGAN PADA PERMUKIMAN DI SEKITAR JALAN TOL KEDUNGMUNDU SEMARANG - Andarina Aji Pamurti (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2021)
The construction of toll roads has a positive impact to facilitate the mobility rate of the community. But the construction of toll roads also has a negative impact on the residential area around the toll road, namely air pollution due to the burning of vehicle fuel. PM2.5 and PM10 air particles are particles that damage the working system of the lungs. The health of the environment where settled is an important support that affects health, especially in the era of pandemic covid. Air particle measurement using portable PM2.5 and PM10 Air Quality Tester Detector. The daily average level of PM2.5 particles in residential areas around Semarang's Kedungmundu toll road is 65.44 μg/Nm³, while the PM10 particle content is 95.2 μg/Nm³. PM2.5 levels exceed the standards of the National Ambient Air Quality Standard (BMUA), The WHO Air Quality Guidline and Ambient Air Quality Standards (USEPA). For PM10 exceeds WHO standard. In addition to air pollution, another impact is that these residential areas have noise. The daily average noise value when measuring the sampling time is 62.23 dB, this value is exceeding the standard threshold of the Regulation of the Minister of Environment for residential areas. So the residential area around Kedungmundu Semarang toll road is less feasible for health when viewed from the value of PM 2.5 and PM10 as well as noise. This study aims to determine the level of PM2.5 and PM10 particles as well as noise in residential areas around the Kedungmundu Semarang toll road. Once the measurement results are obtained, it will be used as a reference for planners to provide solutions for settlements that have an impact due to toll road construction activities with dense vehicle intensity.